2017
DOI: 10.4251/wjgo.v9.i2.62
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in colorectal cancer: Possible roles in regulation of cancer cells

Abstract: Colorectal cancer (CRC) is the third most commonly diagnosed cancer in the world and the fourth principal cause of cancer deaths worldwide. Currently, there is a lack of low cost and noninvasive screening tests for CRC, becoming a serious health problem. In this context, a potential biomarker for the early detection of CRC has recently gained attention. Circular RNAs (circRNA), a re-discovered, abundant RNA specie, is a type of noncoding covalent closed RNAs formed from both exonic and intronic sequences. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 51 publications
1
59
0
Order By: Relevance
“…Recent studies demonstrate that circRNAs dysregulation is intimately associated with human disorders, as they are aberrantly expressed in colorectal cancer (CRC; Taborda, Ramírez, & Bernal, 2017), gastric cancer (P. Li et al, 2015), basal cell carcinoma (Sand et al, 2016), and reproductive system cancers, such as ovarian cancer fibrosis (Bachmayr‐Heyda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that circRNAs dysregulation is intimately associated with human disorders, as they are aberrantly expressed in colorectal cancer (CRC; Taborda, Ramírez, & Bernal, 2017), gastric cancer (P. Li et al, 2015), basal cell carcinoma (Sand et al, 2016), and reproductive system cancers, such as ovarian cancer fibrosis (Bachmayr‐Heyda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4 The exact mechanisms where osteosarcoma develops and progresses are unclear none the less, so determining the molecular development mechanism of osteosarcoma becomes the top priority for diagnosing and treating the disease. 9 Research has manifested that circRNAs are found in cancer cells and show abnormal expressions in such epithelial cancers as lung cancer, 10 gastric cancer 11 and osteosarcoma. 6 Despite over 40 years of investigation on circRNAs, 7 little attention has been paid to them until recently.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, ncRNAs, such as miRNAs, lncRNAs are involved in the development and progression of CRC . However, as a novel identified ncRNAs, the relationship between circRNAs and CRC development is still unknown …”
Section: Introductionmentioning
confidence: 99%